Treatment of deep vein thrombosis from Iranian traditional medicine and modern medicine points of view: comparative study (Iranian Society of Pharmacognosy, 2017)
Background and objectives: Recently, deep vein thrombosis (DVT) has remained a major cause of morbidity and death. DVT is a serious public health issue and can be complicated by pulmonary embolism and stroke leading to high economic burden. Disease etiologies may include protein C deficiency, protein S deficiency, factor V Leiden gene mutation, prothrombin gene 20210A mutation, antithrombin III deficiency, immobilization, malignancy, nephrotic syndrome, antiphospholipid antibody syndrome, estrogen use, pregnancy and hyperhomocystinemia. From Iranian traditional medicine (ITM) point of view, increased blood viscosity is the main cause of DVT. In this study, treatment of DVT has been investigated in ITM comparing with modern medicine. Methods: All data for this review were obtained by search engines such as Google Scholar, Pub Med, SID, and Iranmedex using key words including "deep vein thrombosis" and "treatment". Results: At present, there is no definite cure for the treatment of DVT in modern medicine and usually anticoagulant drugs such as, low-molecular-weight heparin, unfractionated heparin and warfarin, inferior vena cava filters, catheter-directed thrombolytic therapy and hybrid operative thrombectomy, are recommended; however, herbal remedies have attracted lots of attention and in this regard, sumac (Rhus coriaria), garlic (Allium sativum), turmeric (Curcuma longa) and barberry) Berberis vulgaris (have been found effective for the treatment of DVT which have been frequently recommended in ITM. Conclusion: In this study, some useful dietary strategies have been presented for the management of DVT which can be helpful for further drug discovery developments.